2021
DOI: 10.5755/j02.mech.25044
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Electrolyte Polishing of Titanium and Niobium Alloys in Low Concentrated Salt Solution Based Electrolyte

Abstract: Today, world enterprises specializing in the production of titanium and niobium alloy products and having modern high-tech equipment are still forced to use outdated, costly and environmentally unsafe methods of polishing and surface cleaning, based on electrochemical treatment in toxic solutions. The complex geometric shape of the processed products does not allow the use of mechanical polishing methods, due to high labor costs and low efficiency. These materials are difficult to process, and the processes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Electrolyte plasma polishing is an innovative and environmentally friendly metal surface processing method known for its high quality and efficiency. It enables the processing of complex-shaped parts with remarkable effectiveness [1][2][3]. By utilizing a low-concentration inorganic salt-based electrolyte, this method presents a favorable alternative to the use of strong acid and alkali electrolytes in traditional electropolishing.…”
Section: Introductionmentioning
confidence: 99%
“…Electrolyte plasma polishing is an innovative and environmentally friendly metal surface processing method known for its high quality and efficiency. It enables the processing of complex-shaped parts with remarkable effectiveness [1][2][3]. By utilizing a low-concentration inorganic salt-based electrolyte, this method presents a favorable alternative to the use of strong acid and alkali electrolytes in traditional electropolishing.…”
Section: Introductionmentioning
confidence: 99%
“…Seo et al 21 found that chromium oxide layers treated with plasma electrolytic polishing have better corrosion resistance stability, that is plasma electrolytic polishing process could form more corrosion-resistant oxidation films. Aliakseyeu et al 22 developed a new plasma electropolishing method for titanium and niobium alloys. It was found that the surface roughness change of Nb was much higher than that of Ti with the increase of current density in the analysis range.…”
Section: Introductionmentioning
confidence: 99%